(untitled) (Research, Society and Development, 2021)
The sweet sorghum resembles sugar cane because it has succulent stems and high levels of fermentable sugars, the crop is a renewable source capable of contributing to the increase of ethanol production in the inter-harvest sugarcane. In this way, the sweet sorghum becomes a complementary crop in the plant, in order to maintain and/or increase the ethanol supply in the market. In view of the above, this study aimed to evaluate the agronomic potential of sweet sorghum genotypes based on morphoagronomic characteristics. Twenty-five genotypes of sweet sorghum were evaluated in a randomized block design, with three repetitions, evaluating nine morphoagronomic characteristics. The data were submitted to analysis of variance and the Scott-Knott test at 1% probability, the correlation coefficients between the characteristics were also estimated by Pearson’s correlation coefficient. Based on the results, it can be concluded that there is variability among the genotypes of sweet sorghum for the morphoagronomic characteristics evaluated. The genotypes CMSXS642, CMSXS646 and CMSXS647 performed better in relation to the characteristics evaluated, showing great promise for ethanol production.